The Fifth Symposium on Sound Engineering and Mastering; 40th Open Seminr on Acoustics Rzeszów–Polańczyk, 14–17 September, 1993 - M. SANKIEWICZ; A. SNAKOWSKA (Archives of Acoustics)
The Symposium has been organized in common by the Institute of Telecommunication and Acoustics of the Wrocław Technical University, and the Polish AES Section. The debates were held from the 8 till the 10 September 1993 in a conference centre, lovely situated in a garden quarter of Wrocław city, its northeastern part.